2020
DOI: 10.1002/cmdc.202000402
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Nitroxoline Analogs with Potent Cathepsin B Exopeptidase Inhibitory Activity

Abstract: Nitroxoline, a well‐known antimicrobial agent, has been identified in several independent studies, and on different molecular targets, as a promising candidate to be repurposed for cancer treatment. One specific target of interest concerns cathepsin B, a lysosomal peptidase involved in the degradation of the extracellular matrix (ECM), leading to tumor invasion, metastasis and angiogenesis. However, dedicated optimization of the nitroxoline core is needed to actually deliver a nitroxoline‐based antitumor drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…Nitroxoline was also found to regulate the signaling pathway PTEN/Akt/AMPK/mTOR 28 , 29 , or p53 axle 8 , 30 . Furthermore, nitroxoline has been confirmed to be the inhibition of cathepsin B activity 31 - 35 . Other studies have found EMT could be regulated by cathepsin B, leading to the metastasis of cancer 36 , 37 .…”
Section: Discussionmentioning
confidence: 95%
“…Nitroxoline was also found to regulate the signaling pathway PTEN/Akt/AMPK/mTOR 28 , 29 , or p53 axle 8 , 30 . Furthermore, nitroxoline has been confirmed to be the inhibition of cathepsin B activity 31 - 35 . Other studies have found EMT could be regulated by cathepsin B, leading to the metastasis of cancer 36 , 37 .…”
Section: Discussionmentioning
confidence: 95%
“…This figure also shows 2:1 stoichiometry (two ligands per one metal cation), which was shown to be exact for all other 8-HQ derivatives as well [ 21 ]. The presence and the position of the nitro group, –NO 2 , were shown to be crucial for nitroxoline MOA: none of the other 8-HQ derivatives demonstrate such antibacterial actions [ 15 , 35 ]. The p-position of –NO 2 reinforces hydroxide group acidity, enhancing the chelating ability for the abovementioned reasons [ 86 ].…”
Section: Nitroxolinementioning
confidence: 99%
“…This has led to a revival of research regarding antibiotics, including the discovery of new ones, developing the existing ones using new tools and techniques, or re-examining and repurposing the old ones. The example depicting the latter case is nitroxoline [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ], one of the oldest antibiotics, which does not belong to any of the typical antibacterial classes [ 20 , 21 ]. Chemically, it is a derivative of 8-hydroxyquinoline, and as such it belongs to a group of molecules with a so-called “privileged structure”, giving it a rich diversity of biological properties [ 22 ].…”
Section: Introductionmentioning
confidence: 99%